Carvacrol Arrests the Proliferation of Hypopharyngeal Carcinoma Cells by Suppressing Ornithine Decarboxylase and Hyaluronidase Activities - Fatima, Kaneez; Luqman, Suaib; Meena, Abha (Frontiers in Nutrition, 2022)
Carvacrol, a monoterpene, is present in the essential oil of Origanum majorana, Origanum vulgare, Thymus vulgaris and Lippia graveolens. It is used in food as flavouring and preservative agent, in cosmetics and medicines because of its bioactivities useful in clinical practice. However, carvacrol was not much explored for its anticancer potential. In this study, efficacy of carvacrol was investigated against deregulated cancer biomarkers/targets in FaDu, K562 and A549 cell lines. Further, the potency of carvacrol was confirmed by quantitative real-time PCR analysis and molecular docking studies. The in vivo anticancer potential of carvacrol was performed on mice S-180 tumor model and the toxicity examination was accomplished through ex vivo, in silico, and in vivo approaches. Carvacrol significantly impeded the growth of FaDu, K562 and A549 cell lines with IC50 values ranging from 9.61±0.05 to 81.32±11.83 µM. Further, the efficacy of carvacrol was explored against different cancer targets in FaDu, K562 and A549 cell lines. Carvacrol inhibits the ODC, COX-2, LOX-5 and HYAL activity in the FaDu cell line and ODC, COX-2, and HYAL activity in the K562 cell line. The results were validated by expression analysis revealing the downregulation of the targeted gene with a significant change in the transcript level of ODC and HYAL in the FaDu cell line with a fold change of 1.56 and 1.61, respectively. A non-significant effect of carvacrol was observed on the downstream signalling pathway of PI3K and HIF-1α/VEGF in FaDu cells. The cell cycle, ROS, MMP, and Annexin V-FITC experiments demonstrate that carvacrol induces apoptosis of FaDu cells. Further, the potency of carvacrol was also evaluated in vivo on mice S-180 tumor model, wherein it inhibits tumor growth (72%) at 75 mg/kg bw. ADMET (in silico) studies predicted carvacrol as a safe molecule. Overall, carvacrol delayed the growth of FaDu, K562 and A549 cell lines by targeting enzymes involved in carcinogenesis process. The existence of one hydroxyl group at the para position of carvacrol could be responsible for the anti-proliferative activity. Thus, carvacrol can be used as a pharmacophore to develop a safe and effective multi-targeted anti-cancer medicament.